Polyurethane polymers. - Thomas, Sabu; Datta, Janusz; Jozef, Haponiuk; R., Arunima (Elsevier, 2017)
Polyurethane Polymers: Composites and Nanocomposites concentrates on the composites and nanocomposites of polyurethane based materials. Polyurethane composites are a very important class of materials widely used in the biomedical and industrial field that offer numerous potential applications in many areas. This book discusses current research and identifies future research needs in the area.
Keywords: Polyurethanes.; elektronické knihy; electronic books